A prospective study on morphological alteration of megakaryocytes amongst megaloblastic anemia cases along with their clinic-haematological manifestations - Mansuri, Benazeer; Thekdi, Komal P. (International Journal of Research in Medical Sciences, 2017)
Background: Megaloblastic anemias are hematologic disorders in which abnormal DNA synthesis causes blood and bone marrow disorders. The cause of thrombocytopenia in megaloblastic anemia has been postulated as hypoproduction in some studies, whereas ineffective thrombopoeisis has been proposed in other. Objective was to study spectrum of clinic-hematological features in megaloblastic anemia and comparative bone marrow aspiration study of thrombocytopenia secondary to megaloblastic anemia, hypoproduction and hyper-destruction. This study was done to understand the various megakaryocytic alterations in hematological disorders presenting with thrombocytopenia due to different mechanisms. Methods: Total 85 cases of thrombocytopenia included in the study. Bone marrow finding in 33 cases of thrombocytopenia of megaloblastic etiology were compared with 34 cases of marrow proven hypo productive thrombocytopenia (aplastic anemia, acute leukemia) and 19 cases of hyper destructive thrombocytopenia (immune thrombocytopenia). Results: Most common age group presenting megaloblastic anemia is 11-20 year, with male to female ratio is1.2:1, most common complaint were generalized weakness and fever. In megaloblastic anemia 24.33%, 60% and 15.67% of the cases shows increase, decrease and normal megakaryocytes respectively. Dysplastic megakaryocytes were observed in 24.3%, 27% and 20.5% of the cases of megaloblastic anemia, acute leukaemia and immune thrombocytopenic purpura respectively. Conclusions: Both hypoproduction and ineffective thrombopoiesis are the underlying path mechanisms in megaloblastic thrombocytopenia as evidenced by the marrow findings. We hereby infer that megaloblastic thrombocytopenia is to be included as a separate category apart from hypo proliferative and hyper destructive groups. The presence of dysplastic megakaryocyte should not prompt an interpretation